EMISI RADIASI MEDAN ELEKTROMAGNETIK KABEL KOMUNIKASI BROADBAND - Sumarni Mardjoeki (Jurnal Teknologi Dirgantara, 2004)
Broadband communication technology transmits data in high speed. Broadband communications using aerial cable as its transmission medium, will radiate electromagnetic field into its surrounding environment. The radiated electromagnetic field is a potential source of interference, especially with other frequency radio devices, which are operated in the same frequency range. In this case, the long wires carrying broadband signals will generate a radio frequency electromagnetic emission. This paper makes a study about interference from the xDSL (Digital Subcriber Line) communication broadband signals, which using an existing telephone subscriber loop cable network as its transmission medium. Generally, the subsciber loop cable is an aerial cable. In order to make the radiation influence does not impact the other radio equipment performance, the standard CISPR 22 regulates the limits, which are 35 dBuV (average) at a distance of 30 for Class A (industrial) equipment and at a distance of 10 m for Class B (residential) equipment.